A influência dos elementos mercadológicos na escolha dos consumidores por marcas populares: uma investigação no mercado residencial de água mineral 20 litros em Fortaleza - Aragão, Daniel Ribeiro (2007)
This dissertation analyzed the work orientation of sales representatives in the market of Fortaleza. It was done through the use of SOCO scale (Sales Orientation - Customer Orientation). The use of the scale had the objective to measure the degree of commitment of the sales representatives during an oriented sale to doctors, helping them make buying decisions that will satisfy their necessities. The sales representatives’ orientation was analyzed using their own opinions along with the doctors’ opinion, besides being those compared to the respective perceptions about work orientation of the sales representative. The following study was based on the prior conjecture that the orientation of the sales representative in Fortaleza is customer oriented, in the representative’s opinion, as well as in the doctor’s opinion. In order to reach the proposed objectives, the following study approaches marketing and the company’s orientation for the market, the mix of marketing communication, as well as the pharmaceutical industry. The qualitative research, referred here, was done during October of 2006. It was done through the use of questionnaires with SOCO scale. The descriptive investigation was focused on gathering opinions of doctors and of sales representatives, which referred to their work orientation. To fulfill the objective of the referred study, different techniques were used, such as: frequency distribution, presentation of bar graphics, normality test, central tendency test, average test and test of difference of average. The non probabilistic sample was composed by 40 doctors and 40 sales representatives. Ultimately, based on the results obtained, the field research which was presented showed that the doctors don’t see the sales representative so oriented to the customer (the doctors themselves, on this matter) as much as the sales representatives see themselves. The following study has also allowed identifying the discrepancy existing among the doctors’ and the sales representatives’ perception of work orientation of the sales representative.